Variations in lower body stiffness during sports-specific tasks in well-trained female athletes - Millett, E. L.; Moresi, M. P.; Watsford, M. L.; Taylor, P. G.; Greene, D. A. (Sports Biomechanics, 2021)
The present study aimed to assess the differences in leg stiffness and the associated performance variables between athletes from various training backgrounds during tasks relevant to athletic training. Forty-seven female participants (20 nationally identified netballers, 13 high-level endurance athletes and 14 age-matched controls) completed a sprint, anticipated sidestep change of direction and unilateral repetitive hopping task to assess leg stiffness and the relationship of stiffness between the different tasks. Leg stiffness and performance variables were evaluated with a 10-camera motion analysis system and force plate, and leg stiffness was derived through the McMahon and Cheng methodology (1990). Significant differences were evident in leg stiffness, and the contributing performance variables between groups across all assessed tasks (p<0.001-0.017). Furthermore, results indicated the control group displayed no leg stiffness relationship between the evaluated tasks, while the stiffness relationship between tasks within athletic populations reflected training-specific demands of athletes. The results of this study indicated that the athletic training background of individuals may contribute to inherent leg stiffness differences between groups. Furthermore, the stiffness relationship observed between tasks suggests practitioners should take care in the selection of task used to monitor leg stiffness from a performance or injury risk perspective.